Decisions Under Uncertainty: Comment - Brewer, K. R. W. (Quarterly Journal of Economics, 1963)
Journal Article Decisions Under Uncertainty: Comment Get access K. R. W. Brewer K. R. W. Brewer Commonwealth Bureau of Census and Statistics, Canberra, A.C.T. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 1, February 1963, Pages 159–161, https://doi.org/10.2307/1879380 Published: 01 February 1963